Những câu hỏi liên quan
VC
Xem chi tiết
B3
Xem chi tiết
NM
24 tháng 9 2021 lúc 7:50

\(1,\\ 1,=15\left(x+y\right)\\ 2,=4\left(2x-3y\right)\\ 3,=x\left(y-1\right)\\ 4,=2x\left(2x-3\right)\\ 2,\\ 1,=\left(x+y\right)\left(2-5a\right)\\ 2,=\left(x-5\right)\left(a^2-3\right)\\ 3,=\left(a-b\right)\left(4x+6xy\right)=2x\left(2+3y\right)\left(a-b\right)\\ 4,=\left(x-1\right)\left(3x+5\right)\\ 3,\\ A=13\left(87+12+1\right)=13\cdot100=1300\\ B=\left(x-3\right)\left(2x+y\right)=\left(13-3\right)\left(26+4\right)=10\cdot30=300\\ 4,\\ 1,\Rightarrow\left(x-5\right)\left(x-2\right)=0\Rightarrow\left[{}\begin{matrix}x=2\\x=5\end{matrix}\right.\\ 2,\Rightarrow\left(x-7\right)\left(x+2\right)=0\Rightarrow\left[{}\begin{matrix}x=7\\x=-2\end{matrix}\right.\\ 3,\Rightarrow\left(3x-1\right)\left(x-4\right)=0\Rightarrow\left[{}\begin{matrix}x=\dfrac{1}{3}\\x=4\end{matrix}\right.\\ 4,\Rightarrow\left(2x+3\right)\left(2x-1\right)=0\\ \Rightarrow\left[{}\begin{matrix}x=-\dfrac{3}{2}\\x=\dfrac{1}{2}\end{matrix}\right.\)

Bình luận (0)
NN
Xem chi tiết
NT
17 tháng 11 2023 lúc 22:01

\(x^5+x^4+2x^3-1\)

\(=x^5+x^4+x^3+x^3-1\)

\(=x^3\left(x^2+x+1\right)+\left(x-1\right)\left(x^2+x+1\right)\)

\(=\left(x^2+x+1\right)\left(x^3+x-1\right)\)

Bình luận (1)
PL
Xem chi tiết
NQ
23 tháng 11 2017 lúc 19:40

x^4+x^2+1 = (x^4+2x^2+1)-x^2 = (x^2+1)^2-x^2 = (x^2-x+1).(x^2+x+1)

k mk nha

Bình luận (0)
PL
23 tháng 11 2017 lúc 19:44

bạn ơi bạn chưa bớt 2x^2 kìa

Bình luận (0)
TN
15 tháng 2 2022 lúc 19:38

ngu dốt

Bình luận (0)
 Khách vãng lai đã xóa
PL
Xem chi tiết
TN
23 tháng 11 2017 lúc 21:54

x5-x4-1=x5-x3-x2-x4+x2+x+x3-x-1

=x2.(x3-x-1)-x.(x3-x-1)+(x3-x-1)

=(x3-x-1)(x2-x+1)

Bình luận (0)
NQ
23 tháng 11 2017 lúc 21:11

x^4+x^2+1 = (x^4+2x^2+1)-x^2 = (x^2+1)^2-x^2 = (x^2-x+1).(x^2+x+1)

k mk nha

Bình luận (0)
VM
23 tháng 1 2022 lúc 20:15

mik chịu

Bình luận (0)
 Khách vãng lai đã xóa
AN
Xem chi tiết
DH
Xem chi tiết
PT
19 tháng 11 2024 lúc 20:48

Cưu là mình vs (x^2+x)^2-2(x^2+x)-15

Bình luận (0)
NL
Xem chi tiết
NP
Xem chi tiết
TH
10 tháng 11 2016 lúc 20:48

x5 + x4 + 1

= x5 - x3 - x2 - x4 + x2 + x + x3 - x - 1

= x2 ( x3 - x - 1) - x ( x3 - x - 1) + 1 ( x3 - x - 1)

= ( x3 - x - 1) ( x2 - x + 1 )

 

Bình luận (0)
NP
10 tháng 11 2016 lúc 20:36

yeu

Bình luận (0)